2015
DOI: 10.1002/j.0022-0337.2015.79.1.tb05856.x
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Dental Students to Interact with Survivors of Traumatic Events: Development of a Two‐Day Module

Abstract: Dentists are likely to treat patients who have experienced a wide range of traumatic life events, including child abuse and neglect, domestic violence, sexual assault, elder abuse, and exposure to combat. In order to effectively treat survivors of traumatic events, dentists must understand how these patients may present in oral health settings, the basic mandated reporting requirements related to abuse and neglect, and communication strategies to help engage trauma survivors in dental treatment. A traditional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 21 publications
(16 reference statements)
0
48
0
Order By: Relevance
“…The remaining articles primarily examined students’ perceptions of CoST components, such as satisfaction, confidence in the material, or perceived benefit 10 , 20 25 . Most of the components assessed in these articles aimed to promote general communication skills, but some included focus on additional topics, such as cultural safety, 11 , 17 , 18 trauma and adverse events, 15 , 25 and nonverbal communication 13 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining articles primarily examined students’ perceptions of CoST components, such as satisfaction, confidence in the material, or perceived benefit 10 , 20 25 . Most of the components assessed in these articles aimed to promote general communication skills, but some included focus on additional topics, such as cultural safety, 11 , 17 , 18 trauma and adverse events, 15 , 25 and nonverbal communication 13 …”
Section: Resultsmentioning
confidence: 99%
“…A number of course structure‐related considerations were discussed by studies included in this review. The most common of these described the importance of integrating content at appropriate periods throughout the dental curriculum 10 , 15 , 16 . Closely tied to this point was the observation that students with more clinical experience tended to view training as less important or helpful to them, perhaps as a result of having more patient contact 19 , 22 .…”
Section: Resultsmentioning
confidence: 99%
“…2 Trauma survivors including DV victims usually are presented to the dental clinic in the acute phase of injury or as a routine dental care appointment showing dental anxiety or unhealthy habits. 15 Dentists are not familiar with DV cases, and including the topic of DV in the dental curriculums will enhance their diagnostic skills and clinical training. 16 Although deferent complex barriers could prevent victims from revealing violence to health care providers, service providers should express acknowledgment and support to victims.…”
Section: Discussionmentioning
confidence: 99%
“…In a study published by Raja et al, a traditional lecture‐format educational module on TIC was developed and implemented for second‐year dental students at a U.S. dental school. In this study, while students began the module as neutral or somewhat confident in treating survivors of trauma, the results showed that they were in fact unable to appropriately document abuse or understand what would be effective methods for managing such patients 11 …”
Section: General Recommendations In the Dental Treatment For Childrenmentioning
confidence: 87%
“…While child maltreatment is a global problem with severe life‐long consequences, there is scarce information in dentistry regarding the patient's emotional approach in this context. As mentioned by Raja et al, while there are educational efforts related to dentistry and maltreatment, such efforts are focused on training oral health practitioners on mandate reporting 11 . While mandated reporting is important, it is only one aspect of providing quality, necessary, and patient‐centered care.…”
Section: Introductionmentioning
confidence: 99%